Determination of Tax Compliance: The Role of Tax Sanctions, Tax Rates, and Tax Technology in Medan City - Irma Herliza Rizki (Outline Journal of Economic Studies, 2026)
Purpose: This study aims to analyze the effect of tax sanctions, tax rates, and tax technology on taxpayer compliance in Medan City. Methods: This study used a quantitative approach with associative research methods. Data were collected through questionnaires distributed to 100 taxpayers in Medan City using purposive sampling techniques. The data analysis method used was multiple linear regression analysis supported by classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests. Results: The results showed that tax sanctions had a positive and significant effect on taxpayer compliance. Tax rates also positively and significantly affected taxpayer compliance. Furthermore, tax technology was found to have the most dominant influence on taxpayer compliance. Simultaneously, tax sanctions, tax rates, and tax technology significantly influenced taxpayer compliance in Medan City. Conclusions: The study concludes that effective tax sanctions, fair tax rates, and the implementation of digital tax technology can improve taxpayer compliance. Tax technology plays an important role in facilitating tax administration and increasing taxpayer awareness. Originality/value: This study provides empirical evidence regarding the combined role of tax sanctions, tax rates, and tax technology in improving taxpayer compliance, particularly in Medan City during the digital taxation era.